Estimating the 'value at risk' of EUA futures prices based on the extreme value theory. (23rd January 2012) - Mi, Zhi-Fu; Zhang, Yue-Jun
This paper employs the Extreme Value Theory (EVT) to measure the 'Value at Risk' (VaR) of EUA futures prices. The results show that during the sample period: first, the EVT approach can be used to reliably measure the extreme risk of carbon futures markets of the European Union Emissions Trading Scheme, both for Phase I and Phase II. Second, the downside extreme risk of carbon futures market outweighs the upside risk, with evident asymmetric features. Moreover, the average VaR of carbon futures contract DEC10 proves much less than that of contract DEC07 during the sample period.